Gurdev Singh's Supreme Court & National Commission on consumer law cases : a compendium of the Supreme Court & National Commission judgments on consumer law, 1986 [i.e., 1996]-2005. - Gurdev Singh (Advocate) (Singla Law Agency, 2005)
Collection of judgments and orders of Supreme Court of India and National Consumer Disputes Redressal Commission on consumer cases.